Exploring Tax Risk: Its Impact on Corporate Risk in Business Tax Strategies - Fatchan, Ilham Nuryana; Laila Oshiana Fitria Azizah; Pramurindra, Rezky; Winarni, Dwi (Riset Akuntansi dan Keuangan Indonesia, 2025)
This study aims to explore the influence of tax avoidance, tax risk, and tax reporting aggressiveness on corporate risk in manufacturing companies listed on the Indonesia Stock Exchange for the 2021–2024 period. Using a quantitative approach and panel data regression method, the study analyzes 140 data points from 35 selected sample companies. The results show that tax avoidance significantly reduces corporate risk when the strategy is conducted legally and managed properly, supporting the argument that tax efficiency can enhance a company’s financial stability. Conversely, tax risk and aggressive tax reporting do not have a significant effect on corporate risk, indicating that companies with good governance and tax mitigation are able to control fiscal uncertainty without increasing business risk potential. The study also highlights the importance of transparency, clarity of tax strategy, and continuous training for financial teams in facing regulatory dynamics and maintaining corporate reputation in the eyes of investors and the public. These findings reinforce international research published in reputable journals while providing policy recommendations for corporate management and regulators to integrate tax risk management into business strategies proactively and sustainably. Thus, this study broadens the understanding of the relationship between tax strategies and corporate risk while guiding business practices toward more adaptive and competitive governance amid global business environment volatility.